Bistable carbon-vacancy defects in h-BN - Li, Song; Gali, Adam (Frontiers in Quantum Science and Technology, 2022)
Single photon emitters in hexagonal boron nitride have been extensively studied recently. Although unambiguous identification of the emitters is still under intense research, carbon related defects are believed to play a vital role for the emitter producing zero-phonon-lines in the range of $1.6$ to $2.2$~eV. In this study, we systematically investigate two configurations of carbon-vacancy defects, \vncb\ and \cnvb, by means of density functional theory calculations. We calculated the reaction barrier energies from one defect to the other to determine relative stability. We find the barrier energies are charge dependent and \cnvb\ could easily transform to \vncb\ in neutral and positive charge states while it is stable when negatively charged. Formation energy calculations show that the \vncb\ is relatively more stable than \cnvb. Our results indicate that the origin of the $1.6$-to-$2.2$-eV emitters should be other carbon-related configurations.